(untitled) (Praxis Educativa, 2026)
This study analyses the historical evolution of education as a core axis of integration within MERCOSUR, highlighting its role in building a regional citizenship and facilitating the transition from an economic to a social regionalism. Addressing the limited research connecting educational discourse and regional regulations, this paper examines the bloc’s decisions, resolutions, and recommendations alongside institutional press sources. Using a qualitative approach and documentary analysis, web scraping and systematic review techniques were applied to materials published up to 2024. Findings reveal a progressive institutionalisation of education focused on mobility, inclusion, and cooperation. The study concludes that education has become a strategic component for regional cohesion and sustainable integration in South America.